2019
DOI: 10.1016/j.jid.2018.06.188
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Promote the Spread of Human T-Cell Leukemia Virus Type 1 via Bidirectional Interactions with CD4+ T Cells

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) propagates within and between individuals via cell-to-cell transmission, and primary infection typically occurs across juxtaposed mucosal surfaces during breastfeeding or sexual intercourse. It is therefore likely that dendritic cells (DCs) are among the first potential targets for HTLV-1. However, it remains unclear how DCs contribute to virus transmission and dissemination in the early stages of infection. We show that an HTLV-1-infected cell line (MT-2) and natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…However, it is worth noting that, in some case, i.e. when HTLV-1 accumulated at MDDCs surface without internalization and thus without productive infection, viral transfer and productive T-cells infection was efficient [58].…”
Section: Infection Of Myeloid Cells By Htlv-1mentioning
confidence: 99%
“…However, it is worth noting that, in some case, i.e. when HTLV-1 accumulated at MDDCs surface without internalization and thus without productive infection, viral transfer and productive T-cells infection was efficient [58].…”
Section: Infection Of Myeloid Cells By Htlv-1mentioning
confidence: 99%
“…As for HSV-1, SFVs use HS as an attachment factor [ 30 , 31 ]. Among retroviruses, membrane protrusions of murine leukemia viruses (MLV), HTLV-1 and HIV-1 have been described: some are open ended, allowing the transfer of viral material without exposure to the extracellular surface while others are closed ended and Env-receptor interaction is required for cell-to-cell infection [ 74 78 ]. In addition, viruses can move along such protrusions while being fully exposed to neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, Tanaka et al found that the cellular susceptibility to HTLV-1 infection did not correlate with the expression of GLUT1, HS, or NRP-1 alone [56]. Cell-to-cell transmission of HTLV-1 can occur frequently after interactions between DCs and T cells, as well as between T cells [46,57]. Because DCs, monocytes, macrophages, and B cells express these receptors, they can also be infected with each other in individuals with HTLV-1 [44,58].…”
Section: Cell-to-cell Transmissionmentioning
confidence: 99%